Desenvolvimento de sobremesa de soja probiótica sabor cacau - Speck, Andressa Loise (2013)
This paper is about a soybean made dessert, cocoa flavored, having two formulas: A with 8% and B with 6% of water soluble soybean extract with or without vanilla, lemon and granola flavor. The process of fermentation was monitored via acidity levels expressed in lactic acid (°Dornic). During the fermentation, the acidity was verified using the titration method, where the quantity of NaOH 0,1N in ml spent to titrate the samples was monitored, and physicochemical analysis were done during the shelf life (pH, acidity expressed in lactic acid (°Dornic) e °brix). Sensory tests were run with untrained adults by Lineation in Randomized Blocks. Six samples were analyzed, being A1, A2 and A3 of the formula A, and B1, B2 and B3 of the B one. The obtained data was submitted to statistical descriptive analysis (average values with the respective standard deviation, variance analysis[1] and the differences between the averages compared with the Tukey test at level of 5%). In the shelf life 28-day monitoring, a little decrease in the pH value and an increase in the acidity expressed in lactic acid was observed. Both of the formulas presented the values established by the law within the shelf life. The sensory analysis showed that there wasn’t significant differences between the 6 (six) samples, except the sample number B1 in the flavor attribute, whose average was 5.1, differing statistically from the other samples and other attributes. Except that, all the formulations showed scores in the approval range. About the acceptability index, the samples A3 and B3 got approved in the flavor matter, while the color and the aroma of all of them were above the same index, and for the appearance attributes just the samples A1 and A2 were below the index. The samples A3 and B2 didn’t get approved in the texture matter. Therefore, only the sample B3 got the acceptability index greater than 70% in all of the attributes. Even though some samples weren’t approved in some attributes, to the global impression all of them were accepted by the judges, being considered with good repercussion.